Simultaneous removal of endotoxins, inflammatory mediators and uremic toxins in ICU patients with septic shock: a retrospective cohort study - Theisen, Benjamin; Lichtenstern, Christoph; Nußhag, Christian; Tan, Benjamin; Hölle, Tobias; Weigand, Markus A.; Kalenka, Armin; Fiedler-Kalenka, Mascha (Scientific reports, 2024)
Sepsis, one of the leading causes of death, is still lacking specific treatment. OXIRIS (BAXTER, Deerfield, IL, USA) is the first device allowing combined removal of endotoxins, inflammatory mediators and uremic toxins, alongside fluid balance control. Available data is very limited. This retrospective propensity score-matched cohort study of adult patients with septic shock aimed to evaluate septic shock duration and mortality in patients treated with either standard of care renal replacement therapy (RRT) or RRT with combined hemoadsorption, who were admitted to the interdisciplinary surgical intensive care unit at Heidelberg University Hospital during the years 2018 through 2021. Main outcomes were duration of shock, thirty-day mortality and plasma interleukin-6 levels before and after initiation of hemoadsorption. Included were 117 patients (female, 33%; male 67%); median age: 67 (16) years. After matching: 42 patients (female, 33%; male, 67%); mean age: 59.1 ± 13.8 years. There was no statistically significant difference in septic shock duration (p = 0.94; hazard ratio (HR) 0.97 (95% CI, 0.48-1.97)). Thirty-day survival analysis showed a non-statistically significant survival difference. (p = 0.063; HR 0.43 (95% CI, 0.17-1.09)). A post-hoc 90-day survival analysis revealed statistically significant longer survival and lower death hazard ratio in patients treated with RRT + HA (p = 0.037; HR = 0.42 (95% CI, 0.18-0.99). In conclusion, RRT with combined hemoadsorption of endotoxins, inflammatory mediators and uremic toxins is a modality worth further investigation.